1995
DOI: 10.2307/3578920
|View full text |Cite|
|
Sign up to set email alerts
|

Methods for the Quantification of DNA Double-Strand Breaks Determined from the Distribution of DNA Fragment Sizes Measured by Pulsed-Field Gel Electrophoresis

Abstract: Different methods were used for evaluating data for DNA double-strand breaks (DSBs), as obtained by pulsed-field gel electrophoresis (PFGE) after X irradiation of Chinese hamster ovary cells. A total of 60 data points in the dose range of 0 to 116 Gy, along with repair data for 30 and 60 Gy, were analyzed by four methods: (1) percentage of DNA released from the plug, (2) specific size markers (percentage of DNA less than specific sizes, (3) fragment size distributions and (4) shape of the molecular weight (M) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 23 publications
3
44
1
Order By: Relevance
“…(Table 2). This value confirmed our previous results El-Awady et al, 2001) and also agreed well with other data (range 8 -15  10 À12 dsb/Gy/Da) based on PFGE, from which a number of dsb can be calculated when it is combined with either 125 I-decay, analysis of fragment size distribution after high doses, or restriction digest (Blöcher and Pohlit, 1982;Iliakis et al, 1991a, b;Lawrence et al, 1993;Cedervall et al, 1994Cedervall et al, , 1995Löbrich et al, 1994a, b;Löbrich, 1999, 2003). Only, Ruiz de Almodovar et al (1994) found a much higher induction frequency of about 66 dsb  10 À12 /Gy/Da.…”
Section: Number Of Induced Dsbsupporting
confidence: 92%
See 1 more Smart Citation
“…(Table 2). This value confirmed our previous results El-Awady et al, 2001) and also agreed well with other data (range 8 -15  10 À12 dsb/Gy/Da) based on PFGE, from which a number of dsb can be calculated when it is combined with either 125 I-decay, analysis of fragment size distribution after high doses, or restriction digest (Blöcher and Pohlit, 1982;Iliakis et al, 1991a, b;Lawrence et al, 1993;Cedervall et al, 1994Cedervall et al, , 1995Löbrich et al, 1994a, b;Löbrich, 1999, 2003). Only, Ruiz de Almodovar et al (1994) found a much higher induction frequency of about 66 dsb  10 À12 /Gy/Da.…”
Section: Number Of Induced Dsbsupporting
confidence: 92%
“…Pulsed-field gel electrophoresis (PFGE), currently most widely used, has the advantage to resolve large DNA fragments according to the molecular size permitting, in principle, a direct quantification of dsb. However, the accurate analysis of the profile of the continuous fragment distribution is not trivial Kraxenberger et al, 1994;Cedervall et al, 1995). In addition, PFGE could be complicated by paradoxical migration patterns (Carle et al, 1986;Chu, 1991;Löbrich et al, 1993).…”
mentioning
confidence: 99%
“…We monitored the formation of DNA breaks using pulsed-field gel electrophoresis (PFGE), where the distribution of randomly broken DNA molecules can be determined by DNA migration from the high-molecular-weight chromosomal DNA band (31,32). Exponentially growing cultures were exposed to M. albus VOCs and then embedded in a low-melting-point agarose gel in order to prevent the indirect breakage of genomic DNA during the subsequent cell lysis.…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian cells tolerate several grays of radiation, which is sufficient to induce dozens of breaks simultaneously (12,54). The ability of Ku to anchor newly formed ends to an underlying structure could serve an important function in suppressing illegitimate rejoining of mismatched DNA ends.…”
Section: Discussionmentioning
confidence: 99%